Environmental impacts of large-scale oil palm enterprises exceed that of smallholdings in Indonesia - Lee, J.S.H.; Ghazoul, J.; Barus, B; Obidzinski, K.; Koh, L.P.; Abood, S. (Wiley, 2014)
The expansion of large‐scale oil palm plantations in Indonesia has taken a heavy toll on forests, biodiversity, and carbon stocks but little is known about the environmental impacts from the smallholder sector. Here, we compare the magnitude of forest and carbon loss attributable to smallholdings, private enterprises, and state‐owned oil palm plantations in Sumatra. During 2000–2010, oil palm development accounted for the loss of 4,744 ha of mangrove, 383,518 ha of peat swamp forest, 289, 406 ha of lowland forest, and 1,000 ha of lower montane forest. Much of this deforestation was driven by private enterprises (88.3%) followed by smallholdings (10.7%) and state‐owned plantations (0.9%). Oil palm‐driven deforestation in Sumatra resulted in 756–1,043 Mt of total gross carbon dioxide emissions, of which ∼90% and ∼9% can be attributed to private enterprises and smallholdings, respectively. While private enterprises are responsible for the bulk of environmental impacts, the smallholder oil palm sector exhibits higher annual rates of expansion (11%) compared to private enterprises (5%). Both sectors will need careful monitoring and engagement to develop successful strategies for mitigating future environmental impacts of oil palm expansion.